Z2Z4Z8-Cyclic codes - Aydogdu, Ismail; Gursoy, Fatmanur (SPRINGER HEIDELBERG, 2019)
In this paper we study Z2Z4Z8-additive codes, which are extensions of recently introduced Z2Z4-additive codes. We determine the standard forms of the generator and parity-check matrices of Z2Z4Z8-additive codes. Moreover, we investigate Z2Z4Z8-cyclic codes and give their generator polynomials and spanning sets. We also give some illustrative examples of both Z2Z4Z8-additive codes and Z2Z4Z8-cyclic codes.
Keywords: Generator matrix; Parity-check matrix; Cyclic codes; Z(2)Z(4)Z(8)-additive codes; Mathematics